PERAN LOCUS OF CONTROL, KEBUTUHAN BERPRESTASI DAN ENTREPRENEURSHIP - Asri Laksmi Riani (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2014)
The purpose of this study was to determine the role of personality traits (locus of control) and need for achievement in generating competitive advantage of small and medium-sized enterprises ( SMEs ). The population in this study is the owner/manager/staff enterprise (SME) in Surakarta. The sampling technique was convenience sampling, the respondents were willing to be successfully met and the study's respondents. The analytical used in this study is descriptive analysis. A total of 32 respondents, the obtained results: 1. On the need for achievement, found that: all respondents enjoy their work, the majority of respondents enjoy and love to do challenging work, keep doing the job even though others have given up, and do not mind to work, while others have fun. 2. On the internal locus of control, found that: most of the respondents believe in the ability of self-determination, believe in control of his own plan, believe in control of his own life, believe in success due to his own abilities and skills, believe in the protection of self-interest.